2007
DOI: 10.1161/strokeaha.107.488502
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Is Neuroprotective Against Permanent Focal Cerebral Ischemia in Mice

Abstract: Background and Purpose-Carnosine is a naturally occurring dipeptide with multiple neuroprotective properties. In addition, it is well tolerated in high doses with minimal side effects. The purposes of this study were to determine whether carnosine is neuroprotective in permanent focal cerebral ischemia and to determine potential mechanisms of neuroprotection. Methods-We investigated the efficacy of carnosine in a mouse model of permanent focal cerebral ischemia. The effects of carnosine were investigated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 17 publications
2
83
0
3
Order By: Relevance
“…In the same study, it has also been shown to reduce the accumulation of malondialdehyde, a marker of lipid peroxidation, in the brains of animals subjected to an ischemic episode. Pretreatment with carnosine has also been reported as effective in decreasing infarct size, neuronal damage, and ROS levels in models of permanent cerebral ischemia [14][15][16]. The application of carnosine in vitro has also been reported to be partially effective in protecting neuronal cultures against damage induced by amyloid-␤ (A␤) [17].…”
Section: B Herculano Et Al / Carnosine Rescues Cognitive Declinementioning
confidence: 99%
“…In the same study, it has also been shown to reduce the accumulation of malondialdehyde, a marker of lipid peroxidation, in the brains of animals subjected to an ischemic episode. Pretreatment with carnosine has also been reported as effective in decreasing infarct size, neuronal damage, and ROS levels in models of permanent cerebral ischemia [14][15][16]. The application of carnosine in vitro has also been reported to be partially effective in protecting neuronal cultures against damage induced by amyloid-␤ (A␤) [17].…”
Section: B Herculano Et Al / Carnosine Rescues Cognitive Declinementioning
confidence: 99%
“…3). Recently, carnosine has been shown to protect cultured neurons from oxygen glucose deprivation and to exhibit neuroprotective properties in animal models of global and cerebral ischemia (17,38,39). Therefore, our data suggest that carnosine and anserine may be attractive candidate for treatment of neurodegenerative disorders.…”
Section: Resultsmentioning
confidence: 65%
“…Artery access is achieved by craniotomy and occlusion is verified by laser-Doppler. 5 Controls consist of unligated left MCA and sham operated rats. After 24 h, MCA segments located upstream and downstream to the ligature are investigated for expressional changes of ET, AT and 5-HT receptors at protein (immunohistochemistry) and functional (myograph) level.…”
Section: Discussionmentioning
confidence: 99%